2004
DOI: 10.1182/blood-2003-04-1346
|View full text |Cite
|
Sign up to set email alerts
|

Congenital thrombotic thrombocytopenic purpura in association with a mutation in the second CUB domain of ADAMTS13

Abstract: IntroductionThrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy characterized by a schistocytic hemolytic anemia and consumptive thrombocytopenia with varying degrees of neurologic and renal impairment. The presence of ultralarge von Willebrand factor (VWF) multimers in the plasmas of patients with chronic relapsing TTP during remission that disappear during an attack led to the implication of these multimers in the pathogenesis of the platelet-rich, fibrin-poor thrombi that occlude arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
3
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 24 publications
9
75
3
1
Order By: Relevance
“…The defect may be due to the removal of the central β-strands present in the CUB domain, resulting in the destruction of its architecture, as previously described by Pimanda. 18 Eight different mutations in the first and second CUB domain were reported previously and some were analyzed by in vitro-expression studies, suggesting, consistently with our results, that the CUB domains play a critical role in the biosynthesis and secretion of ADAMTS13. 8,35,36 The 4143_4144insA mutation has been frequently detected in patients with hereditary ADAMTS13 deficiency in northern and central European countries.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The defect may be due to the removal of the central β-strands present in the CUB domain, resulting in the destruction of its architecture, as previously described by Pimanda. 18 Eight different mutations in the first and second CUB domain were reported previously and some were analyzed by in vitro-expression studies, suggesting, consistently with our results, that the CUB domains play a critical role in the biosynthesis and secretion of ADAMTS13. 8,35,36 The 4143_4144insA mutation has been frequently detected in patients with hereditary ADAMTS13 deficiency in northern and central European countries.…”
Section: Discussionsupporting
confidence: 75%
“…[15][16][17][18][19] The present study evaluates the molecular mechanism of two mutations observed in the compound heterozygous state in two Turkish siblings with congenital TTP. One mutation, present on the maternal allele, is a single base (A) insertion mutation located within exon 29 (c.4143_4144insA) in the second CUB domain, leading to a frameshift and loss of the last 49 amino acids of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported mutations are limited to individual families, with two exceptions: 1) Mutation c.4143_4144dupA, where the insertion of a single base (adenine, A) at position 4143_4144 results in a frameshift and loss of 49 amino acids is one of the most frequently reported ADAMTS13 mutations in Caucasians [17][18][19][20][21][22][23] and therefore included in this study. 2) Mutation c.3178C>T (p.Arg1060Trp) in exon 24 is also frequent and associated with late-onset and pregnancy related TTP, and is therefore of special interest in relation to preeclampsia [24,25].…”
Section: Adamts13 Variantsmentioning
confidence: 99%
“…[21][22][23] The cleavage can be stimulated by shear forces like those occurring at sites of arterial thrombosis or by low ionic strength and 1.5 M urea or guanidine. 19,20 Congenital ADAMTS13 deficiency is rare and associated with missense or frame-shift mutations of the ADAMTS13 gene, 18,[24][25][26][27][28][29] whereas acquired ADAMTS13 deficiency is more common and often caused by immunoglobulin G (IgG) inhibitors. 13,[30][31][32][33] Therefore, the efficacy of plasma infusion or therapeutic plasma exchange probably depends on replenishing the missing ADAMTS13 metalloprotease or removing the inhibitory antibodies.…”
Section: Introductionmentioning
confidence: 99%